2021
DOI: 10.1007/s12518-021-00365-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 prediction analysis using artificial intelligence procedures and GIS spatial analyst: a case study for Iraq

Abstract: The prediction of diseases caused by viral infections is a complex medical task where many real data that consists of different variables must be employed. As known, COVID-19 is the most dangerous disease worldwide; nowhere, an effective drug has been found yet. To limit its spread, it is essential to find a rational method that shows the spread of this virus by relying on many infected people’s data. A model consisting of three artificial neural networks’ (ANN) functions was developed to predict COVID-19 sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Furthermore, the Getis-Ord spatial autocorrelation technique was adopted to predict spatial hotspots and coldspots for COVID-19. The results obtained from K-means clustering approach to observe spatially clustered patterns for spread of COVID-19 is consistent with some recent findings Azarafza et al, YYYY , Yahya et al, 2021 . However, to our knowledge, in view of COVID-19 outbreak this study for the first time leveraged Elbow method towards estimating optimal number of clusters and minimizing the ICV to visualize spatial pattern of spread across different districts of Maharashtra.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the Getis-Ord spatial autocorrelation technique was adopted to predict spatial hotspots and coldspots for COVID-19. The results obtained from K-means clustering approach to observe spatially clustered patterns for spread of COVID-19 is consistent with some recent findings Azarafza et al, YYYY , Yahya et al, 2021 . However, to our knowledge, in view of COVID-19 outbreak this study for the first time leveraged Elbow method towards estimating optimal number of clusters and minimizing the ICV to visualize spatial pattern of spread across different districts of Maharashtra.…”
Section: Discussionsupporting
confidence: 91%
“…Other models and statistical tools have been employed to explored COVID-19 cases, deaths, or both. Yahya et al (2021) applied three artificial neural networks (ANN) functions to predict the spread of COVID-19 cases and found that the spread severity is expected to intensify in the next few months (six) by 17.1% while the average deaths by 8.3% with a model performance efficiency reaching 81.6%. The model provided the expected cases and deaths due to the virus for authorities to better plan for the management of the case and death counts in the future.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…AI helps analyze and assess information from reported cases and uses that to predict the situation regarding COVID-19. Yahya et al used the geographic information system and developed an AI model with three artificial networks to predict the impact of COVID- 19 in Iraq [ 14 ]. In addition, they predict the severity in which the virus would spread within the next 6 months and the average death case increase during the upcoming days, which helped develop a plan to combat the social effects of COVID 19 in Iraq.…”
Section: Ai Application For Covid-19 Surveillancementioning
confidence: 99%